1990
DOI: 10.1016/s0006-3495(90)82594-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear mechanisms for gain adaptation in locust photoreceptors

Abstract: Intracellular membrane potential responses were recorded from locust photoreceptors under two stimulus conditions: pairs of flashes to dark-adapted receptors, and white-noise modulated light at a range of background intensities from 500 to 15,000 effective photons per second. Nonlinear analysis of the input-output relationships were performed by estimating the Volterra and Wiener kernels of the system. The Volterra kernels obtained from the double-flash experiments were similar to the Wiener kernels obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
1
13
1
Order By: Relevance
“…In a previous investigation (Pece et al 1990), we suggested that the nonlinear depression observed with a pseudo-random stimulus has the same mechanism as the depression observed with pairs of flashes. We also proposed a biochemical mechanism for both processes, in which the depression is due to enzyme inhibition within the phototransduction cascade.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…In a previous investigation (Pece et al 1990), we suggested that the nonlinear depression observed with a pseudo-random stimulus has the same mechanism as the depression observed with pairs of flashes. We also proposed a biochemical mechanism for both processes, in which the depression is due to enzyme inhibition within the phototransduction cascade.…”
Section: Discussionmentioning
confidence: 75%
“…The difference trace obtained in this way always had a single minimum, as shown in Fig. 1 and in French and Kuster (1985) and Pece et al (1990). The peak depression was taken as a measure of the interaction between the two stimuli, as in French and Kuster (1985).…”
Section: Interactions Between Localized Stimulimentioning
confidence: 80%
See 2 more Smart Citations
“…Researchers have used Wiener/Volterra kernals for system identification to gain insight into the function and mechanisms underlying various biological systems. For example, orthogonalization techniques for estimating the kernel values have been developed and applied to various sensory systems, such as the catfish retina [15], the visual cortex in the cat [16], the locust and fly photoreceptor [17][18][19] and the cockroach tactile spine [20,21]. Recently, researchers have used neural networks in system identification and modeling of various biological systems, such as insect walking [22], renal autoregulation in rats [23], and locomotor oscillators in lamprey spinal cords [24,25].…”
Section: Introductionmentioning
confidence: 99%